The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-10970-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of intravenous thiamine and/or magnesium sulphate administration on erythrocyte transketolase activity, lactate concentrations and alcohol withdrawal scores

Abstract: Alcohol withdrawal syndrome (AWS) occurs in 2% of patients admitted to U.K. hospitals. Routine treatment includes thiamine and benzodiazepines. Laboratory studies indicate that thiamine requires magnesium for optimal activity, however this has not translated into clinical practice. Patients experiencing AWS were randomized to three groups: (group 1) thiamine, (group 2) thiamine plus MgSO4 or (group 3) MgSO4. Pre- and 2-h post-treatment blood samples were taken. AWS severity was recorded using the Glasgow Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…This was in contrast to the use of ETKac cut‐offs that showed no discrimination between cases and controls 17 . The cut‐off value of 0.59 has since been used in other studies, 18,23,35 but remains unsubstantiated. Soukaloun et al 17 .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This was in contrast to the use of ETKac cut‐offs that showed no discrimination between cases and controls 17 . The cut‐off value of 0.59 has since been used in other studies, 18,23,35 but remains unsubstantiated. Soukaloun et al 17 .…”
Section: Discussionmentioning
confidence: 97%
“…This was in contrast to the use of ETKac cut-offs that showed no discrimination between cases and controls. 17 The cut-off value of 0.59 has since been used in other studies, 18,23,35 but remains unsubstantiated. Soukaloun et al 17 also reported reference ranges of between 0.47 and 0.57 U/gHb for children and women aged between 4 and 49 years and derived from UK NDNS data.…”
Section: Uk (B) (A)mentioning
confidence: 99%
See 3 more Smart Citations